Research in unitary water consumption in multifamily building for daily recording - Koral , Wojciech (Instal, 2019)
The paper describes the results of research in unitary water consumption in a multifamily building equipped with smart water meters, read remotely every day for 6 weeks. Water consumption was analyzed for 100 premises, equipped with 391 water meters, along with consumption of hot utility water and the balance difference with the water meter.